Cardiac Microvascular Endothelial Cells in Pressure Overload–Induced Heart Disease. (January 2021) - Trenson, Sander; Hermans, Hadewich; Craps, Sander; Pokreisz, Peter; de Zeeuw, Pauline; Van Wauwe, Jore; Gillijns, Hilde; Veltman, Denise; Wei, Fangfei; Caluwé, Ellen; Gijsbers, Rik; Baatsen, Pieter; et al.
Abstract : Background: Chronic pressure overload predisposes to heart failure, but the pathogenic role of microvascular endothelial cells (MiVEC) remains unknown. We characterized transcriptional, metabolic, and functional adaptation of cardiac MiVEC to pressure overload in mice and patients with aortic stenosis (AS). Methods: In Tie2-Gfp mice subjected to transverse aortic constriction or sham surgery, we performed RNA sequencing of isolated cardiac Gfp + -MiVEC and validated the signature in freshly isolated MiVEC from left ventricle outflow tract and right atrium of patients with AS. We next compared their angiogenic and metabolic profiles and finally correlated molecular and pathological signatures with clinical phenotypes of 42 patients with AS (50% women). Results: In mice, transverse aortic constriction induced progressive systolic dysfunction, fibrosis, and reduced microvascular density. After 10 weeks, 25 genes predominantly involved in matrix-regulation were >2-fold upregulated in isolated MiVEC. Increased transcript levels of Cartilage Intermediate Layer Protein ( Cilp ), Thrombospondin-4, Adamtsl-2, and Collagen1a1 were confirmed by quantitative reverse transcription polymerase chain reaction and recapitulated in left ventricle outflow tract-derived MiVEC of AS ( P <0.05 versus right atrium-MiVEC). Fatty acid oxidation increased >2-fold in left ventricle outflow tract-MiVEC, proline content by 130% (median, IQR, 58%–474%; P =0.008) and procollagen secretion by 85% (mean [95% CI, 16%–154%]; P <0.05 versus right atrium-MiVEC for all). The altered transcriptome in left ventricle outflow tract-MiVEC was associated with impaired 2-dimensional-vascular network formation and 3-dimensional-spheroid sprouting ( P <0.05 versus right atrium-MiVEC), profibrotic ultrastructural changes, and impaired diastolic left ventricle function, capillary density and functional status, especially in female AS. Conclusions: Pressure overload induces major transcriptional and metabolic adaptations in cardiac MiVEC resulting in excess interstitial fibrosis and impaired angiogenesis. Molecular rewiring of MiVEC is worse in women, compromises functional status, and identifies novel targets for intervention. Abstract : Supplemental Digital Content is available in the text.